Ageing effects on the creep‐recovery behavior of blown extruded low density polyethylene film. Issue 46 (6th August 2016) - Benmiloud, N. H.; Sebaa, M.; Chabira, S. F.; Poncot, M.; Royaud, I.
ABSTRACT: Low density polyethylene films used for greenhouse covering were naturally weathered for 6 months in sub‐Saharan region (Algeria). The microstructural and morphological changes have been checked by infrared spectroscopy. The changes of the mechanical properties have been followed by tensile and creep‐recovery tests. The measurements were carried out in the two main directions of the film plane. Besides oxidation, chain scission and crosslinking are competing during all the ageing protocol, affecting thereby, the mechanical properties as well as the viscoelastic behavior revealed by creep‐recovery curves. The anisotropic character of the film is preserved during ageing. The improvement of the creep resistance via crosslinking in both directions, affects the different deformations. The short chain segments coming from chain scissions increase the crystallinity ratio (via a chemo‐crystallization process) lowering by consequence each of the minimum strain rate ( ɛ ̇ min ), the instantaneous ( ɛ a ), and delayed recoveries ( ɛ b   a n d   ɛ c ) as well. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44209. Abstract :